Framework of the Process of Formation and Development of Interorganizational Networks - Antunes, Luiz Guilherme Rodrigues; Anselmo, Nathalia Aparecida; Castro, Cleber Carvalho de (Revista Competitividade e Sustentabilidade, 2025)
This study is a theoretical essay that presents a theoretical framework for forming and developing interorganizational networks, integrating economic and social dimensions, and emphasising the critical role of institutions in emerging markets. By drawing on the foundational theories of Grandori and Soda (1995), Jones et al. (1997), and Larson and Starr (1993), the research examines network formation, coordination mechanisms, and governance structures. Practical examples from both developed and emerging markets are used to highlight how institutional support fosters network evolution. Key findings reveal that interorganizational networks in emerging markets heavily depend on institutions to overcome structural challenges, promote collaborative innovation, and reduce opportunistic behaviours. Mechanisms such as reputation systems and social sanctions are central to ensuring long-term sustainability. The proposed framework contributes significantly to the literature by focusing on emerging markets, a context often underexplored in studies of interorganizational networks. It provides actionable insights for managers and policymakers, offering guidance on leveraging institutions to strengthen network collaboration and promote sustainable development. By addressing resource constraints and unique challenges, the study enhances understanding of network dynamics and their role in driving social inclusion and regional competitiveness.